An empirical analysis of the long-run comovement, dynamic returns linkages and volatility transmission between the world major and the South African stock markets - Chinzara, Zivanemoyo (Rhodes University, Faculty of Commerce, Department of Economics, 2008)
The international linkages of stock markets have important implications for cost of capital and portfolio diversification. Recent trends in globalization, financial liberalization and financial innovation raises questions with regard to whether African stock markets are being integrated into world equity markets. This study examines the extent to which the South African (SA) equity market is integrated into the world equity markets using daily data for the period 1995-2007. The study is divided into three main parts, each looking at the different ways in which integration can be considered. The first investigates whether there is long run comovement between the SA and the major global equity markets. Both bivariate and multivariate Johansen (1988) and Johansen and Juselius (1990) cointegration approaches were utilised. Vector Error Correction Models (VECMs) are then estimated for portfolios which show evidence of cointegration. The second part analyses returns linkages using the Vector Autoregressive (VAR), block exogeneity, impulse response and variance decomposition. The third part examines the behaviour of volatility and volatility linkages among the stock markets. Firstly volatility is analysed using the GARCH, EGARCH and GJR GARCH. Simultaneously, the hypothesis that investors receive a premium for investing in more risky stock markets is explored using the GARCH-in mean. The long term trend of volatility is also examined. Volatility linkages are then analysed using the VAR, block exogeneity, impulse response and variance decomposition. The first part established that no bivariate cointegration exists between the SA and any of the stock markets being studied, implying that pairwise portfolio diversification is potentially worthwhile for SA portfolio managers. However, multivariate cointegration exists for some portfolios, with the US, UK, Germany and SA showing evidence of error correction for some of these portfolios. Findings on return linkages is that there are significant returns linkages among the markets, with the US and SA being the most exogenous and most endogenous respectively. Findings regarding volatility are that the volatility in all the markets is inherently asymmetric and that except for the US there is no risk premium in any of the markets. The long term trend of volatility in all the stock markets was found to be relatively stable. The final finding was that significant volatility linkages exist among the markets, with the US being the most exogenous and SA and China showing evidence of bidirectional linkages. Overall, except for volatility linkages, the integration of SA into the global equity markets is still quite low. Thus, both SA and international investors can capitalise on this portfolio diversification potential. On the other hand, policy makers should capitalise on this and make policies that will attract the much needed foreign investors.
Keywords: Stock exchanges -- South Africa; Globalization -- Economic aspects -- South Africa; International economic relations; Portfolio management -- South Africa; Monetary policy -- South Africa